Pengaruh Employee Engagement Dan Organizational Citizenship Behavior Terhadap Kinerja Karyawan pada UD. Hoshi Creasindo di Kabupaten Bekasi - Kusuma, Aditya Bayu; Maulana, Dede Yusuf; Kinanthi, Hening Lintang; Fachmi, Muhammad; Mardiman (Eqien - Jurnal Ekonomi dan Bisnis, 2025)
Companies need to see how much employees are involved in working and preferred behavior that is not part of an employee's formal work obligations, but supports the effective functioning of the organization in order to achieve optimal employee performance. The purpose of this study was to determine the effect of Employee Engagement and Organizational Citizenship Behavior both partially and simultaneously on Employee Performance. The sample in this study were 47 respondents using saturated sampling as the sampling technique. Data processing in this study used SmartPLS 4.0. The results showed that Employee Engagement has a positive and significant influence on Employee Performance because it has a p values (0,003) < 0,05. The results also show that Organizational Citizenship Behavior has a positive and significant influence on Employee Performance because it has p values (0,000) > 0.05. Finally, it is also known that Employee Engagement and Organizational Citizenship Behavior simultaneously on Employee Performance because it has a p values (0,000) > 0.05